The instruments of soft power within Turkish foreign policy in the post- cold war area : Turkish international cooperation and development agency (tika) as a case of Turkey’s soft power application - Erguvan, Esra (My University, 2010)
Dünya tarihi pek çok köklü değişikliğin yaşandığı çeşitli dönemi içermektedir. Soğuk Savaş dönemi de, iki kutuplu dünyanın bir sonucu olarak yaşanan olayların karmaşıklığı ve siyasi aktörlerin karakteristiği dolayısıyla dünya politikası açısından büyük önem taşımaktadır. Ayrıca, Soğuk Savaş sonrası dönem de, 45 yıllık iki kutuplu Soğuk Savaş dönemine oranla büyük farklar barındırdığından büyük önem arz etmektedir. Bununla birlikte, Soğuk Savaş’ın sona ermesiyle ülkeler arasındaki ilişkilerin boyutu değişirken, yeni tür tehditlerin de ortaya çıktığı gözlenmektedir. Dahası, bu yeni tür tehditlerin, Soğuk Savaş dönemine göre çok farklı çözümler gerektirdiği de ortaya çıkmıştır. Bu doğrultuda, klasik sert güç enstrümanlarına ek olarak, ülkeler tarafından yumuşak güç enstrümanlarının da tartışmaya açıldığı ve uygulamaya geçirildiği görülmektedir. Yukarıda sözü edilenler ışığında, bu çalışmada Soğuk Savaş ve sonrasında Türkiye ve bölge ülkeleri arasındaki ilişkiler ve Türkiye’nin yumuşak güç güç kapasitesi ile enstrümanlarının temel boyutu incelenmiştir. Türk İşbirliği ve Kalkınma İdaresi Başkanlığı (TİKA) ve kurumun dünya üzerinde pek çok bölgede uygulanan projelerinin Türkiye’nin yumuşak gücüne katkısı araştırılmıştır. Yeni bir oluşum olarak, TİKA’nın uluslararası kalkınma yardımları toplumunda pek çok görev ve sorumluluklarının bulunduğu ortadadır. Bu sebeple, TİKA’nın Türkiye’nin yumuşak gücüne katkısının olup olmadığı sorusuna yanıt vermek amacıyla, TİKA projeleri ve bu projelerin yardım alan ülkelerdeki izdüşümleriyle Türkiye’deki yumuşak güç kavramı ve yumuşak güç enstrümanları arasındaki ilişki derinlemesine incelenmiştir. Savaş, Soğuk Savaş Sonrası, Yumuşak Güç, Kalkınma Yardımları, Türk Dış Politikası, Türk İşbirliği ve Kalkınma İdaresi Başkanlığı (TİKA)

The world history has various periods in which tremendous changes took place. The Cold War was one of the most important periods in the world politics due to the complexity of the events and the characteristics of the political actors shaped by the bipolar structure of the world. Furthermore, the end of the Cold War was also of cardinal importance, since the 45 years of bipolarity and the block politics were replaced with a new period which has much different characteristics. With the end of the Cold War, new sets of relations among countries were established while new groups of threats also emerged. These new post-Cold War threats appeared to require new sets of solutions than that of the Cold War. In this context, the theory and instruments of soft power began to be discussed intensively and applied by a number of countries in addition to the classical hard power measures. In line with these discussions, the main dimensions of Turkey’s soft power capabilities and several instruments of soft power were elaborated in this thesis while observing the relations between Turkey and the regional countries during the periods of the Cold War and the post-Cold War as a continuum. Moreover, Turkish International Cooperation and Development Agency (TIKA) and the role of its projects implemented in several regions all over the world, are examined as the sources of Turkey’s soft power. TIKA has several duties and responsibilities in the international development assistance community. The linkage between the concepts and sources of Turkey’s soft power and TIKA’s projects and their outcomes in the recipient countries is analyzed in the thesis in order to answer the question of whether TIKA has a role in wielding Turkey’s soft power. Key Words: Cold War, Post-Cold War, Soft Power, Development Assistance, Turkish Foreign Policy, Turkish International Cooperation and Development Agency (TIKA)
Keywords: Dış İlişkiler; Soğuk Savaş; Uluslararası İlişkiler